High-precision photometry by telescope defocusing: III. The transiting planetary system WASP-2★ - Southworth, John; Mancini, L.; Novati, S. Calchi; Dominik, M.; Glitrup, M.; Hinse, T. C.; Jørgensen, U. G.; Mathiasen, M.; Ricci, D.; Maier, G.; Zimmer, Fabian; Bozza, V.; et al. (Monthly notices of the Royal Astronomical Society, 2010)
We present high-precision photometry of three transits of the extrasolar planetary system WASP-2, obtained by defocusing the telescopes, and achieving scatters of between 0.42 and 0.73 mmag versus the best-fitting model. These data are modelled using the jktebop code, and taking into account the light from the recently discovered faint star close to the system. The physical properties of the WASP-2 system are derived using tabulated predictions from five different sets of stellar evolutionary models, allowing both statistical and systematic error bars to be specified. We find the mass and radius of the planet to be Mb= 0.846 ± 0.055 ± 0.023 MJup and Rb= 1.043 ± 0.029 ± 0.015RJup. It has a low equilibrium temperature of 1281 ± 21 K, in agreement with a recent finding that it does not have an atmospheric temperature inversion. The first of our transit data sets has a scatter of only 0.42 mmag with respect to the best-fitting light-curve model, which to our knowledge is a record for ground-based observations of a transiting extrasolar planetary system.
Gesehen am 04.10.2023